Air pollution consequences in São Paulo: evidence for health - Guidetti, Bruna Morais (2018)
Air pollution causes negative externalities on human health, especially on vulnerable groups such as children. We look at hospitalizations due to respiratory diseases for children in São Paulo Metropolitan Area (SPMA) between 2015 and 2017 as consequence of variation in particulate matter (PM 10) levels. We use wind speed as instrument for PM to deal with the endogeneity of air pollution exposure, considering that non-stationary sources of pollution are predominant in the region, which is among the ten largest metropolitan areas in the world. The results show that air pollution positively affects hospitalizations due to all respiratory, pneumonia and asthma in the short term for children between one and five years old. For infant, we only find impact on influenza admission. Additional results suggest the Brazilian public health system is absorbing the increase in hospitalization due to this health shock. Furthermore, delay to visit the hospital may be underestimating our results. We also run a multi-pollutant model, including ozone (O3) as pollutant and solar radiation as instrument. Our coefficients of PM 10 are robust to this specification and we find no impact of O3 on health.